Gesture-Based Extraction of Robot Skill Parameters for Intuitive Robot Programming - Pedersen, Mikkel Rath; Krüger, Volker (Journal of intelligent & robotic systems, 2015)
Despite a lot of research in the field, only very little experience exists with Teaching by Demonstration (TbD) in actual industrial use cases. In the factory of the future, it is necessary to rapidly reprogram flexible mobile manipulators to perform new tasks, when the need arises, for which a working system capable of TbD would be ideal. Contrary to current TbD approaches, that generally aim to recognize both action and where it is applied, we propose a division of labor, where the operator manually specifies the action the robot should perform, while gestures are used for specifying the relevant action parameter (e.g. on which object to apply the action). Using this two-step method has the advantages that there is no uncertainty of which action the robot will perform, it takes into account that the environment changes, so objects do not need to be at predefined locations, and the parameter specification is possible even for inexperienced users. Experiments with 24 people in 3 different environments verify that it is indeed intuitive, even for a robotics novice, to program a mobile manipulator using this method.